'For She Was an Independent Woman, or Nearly, Anyway': The Sexualisation of Neo-Victorian Girls in Philip Pullman's Sally Lockhart Series. Issue 2 (June 2022) - Burke, Lois
Abstract : Neo-Victorian YA literature has a complex relationship with representing sexualities, due to the limited evidence of youth sexuality that remains from the nineteenth century and the tension between adhering to and revising ideas about this historical period. This relationship is played out in the Sally Lockhart book series (1985–94), in which the attachment to Victorian literary tropes and settings offers a narrow reference of girlhood sexuality and which often presents girl characters as vulnerable to sexual assault. This article questions the books' goals of reimagining the nineteenth century and the messages they send to modern young readers.